The dynamics of capital flow episodes - Christian Friedrich; Pierre Guérin (Bank of Canada, 2016)
This paper proposes a novel methodology for identifying episodes of strong capital flows based on a regime-switching model. In comparison with the existing literature, a key advantage of our methodology is to estimate capital flow regimes without the need for context- and sample-specific assumptions. We implement this approach using weekly fund flows data for a large set of advanced and emerging economies. As an application of our methodology to the global financial cycle literature, we use a time-varying structural vector-autoregressive (VAR) model to assess the impact of U.S. stock market volatility (VIX) shocks and U.S. monetary policy shocks on aggregated measures of equity outflow and equity inflow episodes. Our results indicate that both VIX and U.S. monetary policy shocks had substantially time-varying effects on episodes of strong capital flows over our sample period.
Keywords: F21; F32; G11; 330; International topics; International financial markets; Econometric and statistical methods; Uncertainty and monetary policy